Teaching lactose metabolism: A complex challenge faced with a simple kit - Monti Hughes, Andrea (2007)
We developed an experimental didactic proposal to teach both carbohydrate metabolism and lactose intolerance as the disease related to that metabolism. Therefore, we implemented an empirical strategy consisting of inexpensive and non-toxic components for which students do not need to know any laboratory techniques. The fact that students were able to discuss their own results obtained from the experiments performed in their classroom gave them additional motivation to learn the subject.